Study on perspective taking in online discussions among university students with hearing impairments - A. A. Gareyev; Yu. V. Krasavina; E. P. Ponomarenko; A. A. Shishkina (Russian State Vocational Pedagogical University, 2024)
Introduction. Communication skills are regarded as one of the most essential competencies for deaf and hard-of-hearing (DHH) students in a digital learning environment. This importance is attributed to the unique cognitive and learning characteristics of these students. Aim. The present research aimed to compare the ability of DHH students with their hearing peers to accept different perspectives during online discussions. Methodology and research method. The experiment involved 17 students, consisting of 8 Deaf and Hard of Hearing (DHH) students and 9 hearing students, who participated in online discussions via Telegram chats over a period of six weeks. Within the framework of the chosen qualimetric approach, methods of group expert assessments and a pedagogical council were employed, along with elements of quantitative content analysis. Results. The quality of online discussions and the level of perspective taking are significantly higher among hearing students compared to their DHH peers. When organising these discussions, it is important to consider certain characteristics: hearing students tend to be highly engaged and independent, while DHH students may provide uncompromising and emotional responses, exhibit frequent linguistic errors, and struggle with issues of plagiarism. In light of these observations, recommendations are provided for effectively organising and conducting online discussions with students who have hearing impairments. Scientific novelty. This study represents the first attempt to compare the development of communication skills between DHH students and hearing students in a digital environment. Considering the unique characteristics of the cognitive activities of DHH students, the method for quantitatively assessing these skills was adapted specifically for this group. Practical significance. The study found that online discussions significantly enhance the cognitive engagement of DHH students, potentially fostering the development of their communication skills in a digital environment. The authors recommend strategies for formulating discussion questions, assisting moderators in discussion chats, and establishing procedures for evaluating discussions. These recommendations can be utilised to assess students' online discussions and their ability to consider alternative perspectives.